Indicative Referral Patterns: (Denoting Nouns and Adverbs of Time and Place) - Khudair, Zainab Yaseen; Obaid, Haider Hasan (Al-Adab Journal, 2022)
This study seeks to shed light on one of the important linguistic topics, which is the patterns of indicative referral (signal nouns and adverbs of time and place) in Semitic languages and to highlight its role in the process of analyzing and understanding the linguistic text in an accurate manner. Study the text. The indicative reference is characterized by being one of the modern studies that study the structure of the text. This study is concerned with a general description of the indicative reference term, from which the denoting nouns, the adverbs of time and place, their divisions and types in Semitic languages, and the term denotes being a complement to the subject of the reference. Note that the study of the phenomenon of reference in general and its role in the structure of the text despite its presence in ancient texts, but this study was discovered by modern linguists according to modern linguistic theories and was not referred to in the literature and books of ancient linguists. Where many text, scholars made a great effort in searching for the structure of the text to discover the functions that fall within the science of text, and an interest in textual studies with the grammatical structure of texts in order to clarify the relationships that link the parts of the text and contribute to the establishment of a coherent linguistic unit from the grammatical and semantic aspects. One of the most famous Western scholars who contributed to laying the foundations for the study of this phenomenon in the structure of the text.